2014
DOI: 10.1039/c4sm00092g
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring of the conjugated polyelectrolyte poly[9,9-bis(4-sulfonylbutoxyphenyl)fluorene-2,7-diyl-2,2′-bithiophene] in liquid crystalline C12E4 in bulk water and aligned thin films

Abstract: We report on the conjugated polyelectrolyte 12 mM poly[9,9-bis(4-sulfonylbutoxyphenyl) fluorene-2,7-diyl-2,2'-bithiophene] (PBS-PF2T) mixed in concentrated aqueous 680 mM tetraethylene glycol monododecyl ether (C12E4) in bulk and thin films. A blue-shift in the fluorescence spectrum demonstrates breakup of PBS-PF2T aggregates in bulk aqueous C12E4. Small-angle X-ray scattering data indicate that this mixture follows a very similar phase behaviour to binary mixtures of a pure surfactant with water, including a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 51 publications
3
10
0
Order By: Relevance
“…I (Supplementary data) shows the final frame of the system showing a distinct separation of phases with the polyelectrolyte side chains exposed to the water environment and with backbones embedded in the surfactant, the surfactant has not aggregated into a particularly diffuse phase. These simulations are fully consistent with observations from SAXS [43].…”
Section: Enhancement Of the Emission Quantum Yieldsupporting
confidence: 93%
See 1 more Smart Citation
“…I (Supplementary data) shows the final frame of the system showing a distinct separation of phases with the polyelectrolyte side chains exposed to the water environment and with backbones embedded in the surfactant, the surfactant has not aggregated into a particularly diffuse phase. These simulations are fully consistent with observations from SAXS [43].…”
Section: Enhancement Of the Emission Quantum Yieldsupporting
confidence: 93%
“…However, if the polyelectrolyte has hydrophobic domains, it is suggested that there may be attractive interactions with the nonionic surfactants [103], leading to association. Molecular dynamics simulations in both the micellar [32] and liquid crystalline (this paper and [43]) surfactant concentration regimes demonstrate that these interactions involve both the hydrophobic chain and the ethylene oxide head group of the surfactants. It is possible that similar considerations are valid for other systems involving polyelectrolytes with these surfactants.…”
Section: What Does This Tell Us About Polyelectrolyte-surfactant Intementioning
confidence: 95%
“…These simulations are an expansion on previous studies of the interaction of PBS-PF2T and tetraethylene glycol monodecyl ether (C 12 E 4 ) by Knaapila et al . [27]. These studies included examination of PBS-PF2T mixed into aqueous C 12 E 4 in bulk and thin films.…”
Section: Introductionmentioning
confidence: 99%
“…PBS-PF2T was selected for both this investigation and the previous study involving C 12 E 4 as an archetypal CPE [27]. Fluorene-bithiophene alternating copolymers, for example poly(9,9-dioctylfluorene- co -bithiophene) are commonly used in molecular electronic devices as charge transport layers [31] while the charged sulfonate groups on the termini of each side chain provide solubility in polar solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation